2015
DOI: 10.1111/jcpe.12404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of palatal donor site haemostasis and wound healing after free gingival graft surgery

Abstract: MPE provided faster and continuous haemostasis that made a positive contribution to the early soft tissue healing to some extent but due to limitations; further trials are needed to demonstrate the efficiency of this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 49 publications
2
69
0
2
Order By: Relevance
“…15 Indeed, it has been demonstrated that the corono-apical dimension of the graft and the residual soft tissue thickness over the bone has a significant impact on the experienced post-operative pain. 16,[37][38][39] Harvesting a graft from the superficial palate, thus, avoiding larger blood vessels and nerves in deeper layers has also been considered as one of the main advantages of the FGGT. 16,[37][38][39] Harvesting a graft from the superficial palate, thus, avoiding larger blood vessels and nerves in deeper layers has also been considered as one of the main advantages of the FGGT.…”
Section: Discussionmentioning
confidence: 99%
“…15 Indeed, it has been demonstrated that the corono-apical dimension of the graft and the residual soft tissue thickness over the bone has a significant impact on the experienced post-operative pain. 16,[37][38][39] Harvesting a graft from the superficial palate, thus, avoiding larger blood vessels and nerves in deeper layers has also been considered as one of the main advantages of the FGGT. 16,[37][38][39] Harvesting a graft from the superficial palate, thus, avoiding larger blood vessels and nerves in deeper layers has also been considered as one of the main advantages of the FGGT.…”
Section: Discussionmentioning
confidence: 99%
“…, Keceli et al. ), and all the patients enrolled in this study were evaluated to determine their epithelialization status. As we know, bleeding is the normal component of the surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The most common postoperative complications are pain, burning sensation, and delayed wound healing on the donor site . To reduce postoperative complications and promote wound healing, various hemostatic agents, dressing materials, platelet‐rich fibrin, and analgesics have been used over the years. However, in the relevant literature no ideal agent has been emphasized …”
mentioning
confidence: 99%